Management of abnormal uterine bleeding by northern, rural and isolated primary care physicians: PART I - How are we doing? - Stewart Donna E; Vigod Simone N (BMC, 2002)
Abstract Background Canadian hysterectomy rates have declined in recent years. However, hysterectomy rates for discretionary indications, principally abnormal uterine bleeding (AUB), remain high in some regions. In northern Ontario, hysterectomy rates for women aged 34-45 are almost triple the rates in southern, urban areas. Primary care physicians (family doctors) usually manage AUB initially in these northern areas where a severe shortage of gynecologists exists. Methods We surveyed 194 family physicians in northern Ontario with a case scenario of a pre-menopausal woman with heavy vaginal bleeding to characterize management and to gain physicians' perspectives on the factors that affect it. Results To investigate her heavy vaginal bleeding, only 17% of physicians recommended a pelvic examination for the woman in our case scenario. Most physicians advocated a course of medical therapy before referral to a gynecologist, for whom the average waiting time was seven weeks. However, most physicians recommended referral after only one failed trial of medical treatment. Physicians felt that major deterrents to medical treatments were patient desires for immediate relief and/or permanent solutions, poor patient compliance and the high cost of medication. Only 25% of respondents indicated that they would perform an endometrial biopsy prior to referral. Conclusions Family physicians would benefit from further education on appropriate investigations for AUB, primarily training in pelvic examination and endometrial biopsy techniques, as well as appropriate treatment algorithms. Further research into patient perspectives on treatment options is needed.